Kya Ma Nā Maññ‘ Myi″ Myi″ (s.n.])
Also available in Karen version.Comic about how a Burmese girl was trafficked, forced into prostitution and finally infected with HIV/AIDS because she didn't have knowledge about HIV/AIDS.